1988
DOI: 10.1524/ract.1988.4445.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Detection of Actinides by Laser Resonance Photoionization

Abstract: Actinides, detection of trace amounts /Laser resonance ionization mass spectrometry /Isotope analysis of plutonium AbstractLaser resonance ionization mass spectrometry has been investigated as a method for the detection of trace amounts of actinides. High sensitivity and selectivity can be achieved by three-step photoionization followed by time-of-flight mass analysis. The laser system for photoionization consists of three dye lasers which are pumped simultaneously by a copper vapor laser. For mass determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Three-color, three-step resonant ionization was first reported by Peuser et al 22 using three pulsed dye lasers, which showed a detection efficiency of 10 . Since then, there have been extensive studies on RIMS as an analytical instrument for trace analysis of Pu and other radioactive elements 17 , 23 31 , for fundamental studies of actinides 32 , and in combination with other techniques such as SIMS 30 , 32 , 33 , fast chemical separation 29 , and laser ablation 34 . Worden et al 35 studied two- and three-step resonance ionization pathways using dye lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Three-color, three-step resonant ionization was first reported by Peuser et al 22 using three pulsed dye lasers, which showed a detection efficiency of 10 . Since then, there have been extensive studies on RIMS as an analytical instrument for trace analysis of Pu and other radioactive elements 17 , 23 31 , for fundamental studies of actinides 32 , and in combination with other techniques such as SIMS 30 , 32 , 33 , fast chemical separation 29 , and laser ablation 34 . Worden et al 35 studied two- and three-step resonance ionization pathways using dye lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Interest has also tumed to various mass spectrometry techniques (ICP-MS [10,11], TIMS [12,13]), but those methods are not really adapted for a matrix where uranium is the principal constituent because of isobaric interfering effects. Only Resonance Ionisation Mass Spectrometry (RIMS [14]) would authorize plutonium measurement with remaining uranium in the sample. However, Instrumentation for RIMS does not exist in many laboratories and as a consequence, for the moment, RIMS is not * Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%